1973
DOI: 10.3109/08820137309022789
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-Electron Microscopic Localization of the Encephalitogenic Basic Protein in Myelin

Abstract: t a n f o r d , C a l i f o r n i a , 94304; and t h e Department of Neurology, U n i v e r s i t y of C a l i f o r n i a , San F r a n c i s c o , C a l i f o r n i a , 94122 and t h e Department of Physiology-Anatomy , U n i v e r s i t y o f C a l i f o r n i a , B e r k e l e y , Calif o r n i a , 94708. A b s t r a c t Immuno-electron microscopic s t u d i e s of t h e l o c a l i z a t i o n of e n c e p h a l it o g e n i c b a s i c p r o t e i n demonstrate i t s p r e s e n c e i n t h e major d e n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1974
1974
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…In some reports, MBP has been shown to be inaccessible to anti-MBP antibody unless the membrane is disrupted by mechanical or chemical means (Kornguth and Anderson, 1965; Hern- , 1973;Guarnieri et al, 1974;Sternberger et al, 1978). Labelling of isolated, intact spinal cord from the cat suggested that MBP was inaccessible to the chemical labelling reagents used (Poduslo and Braun, 1975;Golds and Braun, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some reports, MBP has been shown to be inaccessible to anti-MBP antibody unless the membrane is disrupted by mechanical or chemical means (Kornguth and Anderson, 1965; Hern- , 1973;Guarnieri et al, 1974;Sternberger et al, 1978). Labelling of isolated, intact spinal cord from the cat suggested that MBP was inaccessible to the chemical labelling reagents used (Poduslo and Braun, 1975;Golds and Braun, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Mendell and Whitaker (1978) localized P, (MBP of the PNS) to the IPL in sciatic nerve myelin by immunoelectron microscopy but were unable to localize MBP in the CNS myelin. Other researchers have localized MBP to the major dense line in vitro and in vivo (Herndon et al, 1973;Poduslo and Braun, 1975;Roussel and Nussbaum, 1981), while Omlin and colleagues (Omlin et al, 1982) localized MBP in the CNS and PNS to the MDL. Although some staining at the IPL was observed also, Omlin et al, 1982 regarded this minor staining pattern as non-specific labelling.…”
Section: Introductionmentioning
confidence: 99%
“…MBP represents 5-15 % of PNS myelin protein [118] and is a highly basic extrinsic membrane protein present at the cytoplasmic surfaces of compact myelin membranes [119][120][121][122][123]. The human MBP contains 170 amino acids including 12 lysine, 19 arginine, 2 glutamic acid and 9 aspartic acid residues.…”
Section: D) Myelin Basic Protein (Mbp)mentioning
confidence: 99%
“…The use of immunochemical techniques in an attempt to localize the CNS myelin basic protein have provided similar findings, namely, that the basic protein is essentially inaccessible to anti-basic protein antibody in intact myelin and only becomes accessible when the membrane is disrupted (Kornguth and Anderson, 1965;Tomasi and Kornguth, 1968;Herndon et al, 1973;Guarnieri et al, 1974).…”
Section: B Myelin Proteins and Lipid-protein Interactionsmentioning
confidence: 90%